2016
DOI: 10.1021/acs.jmedchem.6b00640
|View full text |Cite
|
Sign up to set email alerts
|

Small Antimicrobial Agents Based on Acylated Reduced Amide Scaffold

Abstract: Prevalence of drug-resistant bacteria has emerged to be one of the greatest threats in the 21st century. Herein, we report the development of a series of small molecular antibacterial agents that are based on the acylated reduced amide scaffold. These molecules display good potency against a panel of multidrug-resistant Gram-positive and Gram-negative bacterial strains. Meanwhile, they also effectively inhibit the biofilm formation. Mechanistic studies suggest that these compounds kill bacteria by compromising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
48
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 50 publications
1
48
0
3
Order By: Relevance
“…To this end, a new series of bis-cyclic guanidine compounds (MW 600‒900 Da) were synthesized (Figure 2), and tested against a panel of multidrug resistant bacteria (Table 1). 16 As expected, some compounds showed exceptional in vitro and in vivo activity. When R 1 was kept as the phenyl group and R 2 was just proton (no substituent), no activity was detected for 1 and 2 with aliphatic (C 4 H 8 ) or aromatic ( m -phenylene) linker under the tested condition.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…To this end, a new series of bis-cyclic guanidine compounds (MW 600‒900 Da) were synthesized (Figure 2), and tested against a panel of multidrug resistant bacteria (Table 1). 16 As expected, some compounds showed exceptional in vitro and in vivo activity. When R 1 was kept as the phenyl group and R 2 was just proton (no substituent), no activity was detected for 1 and 2 with aliphatic (C 4 H 8 ) or aromatic ( m -phenylene) linker under the tested condition.…”
supporting
confidence: 59%
“…Such mechanisms also confer HDPs with broad-spectrum bactericidal activity. 4, 16 It should be noted that some HDPs do have defined intracellular targets besides their membrane- disruptive activity, nonetheless, these combined mechanisms of actions could indeed further synergize their antimicrobial activity. 13 Despite enthusiasm, there are obstacles associated with antibiotic HDPs and HDP-mimicking oligomeric peptidomimetics, 1719 including difficulty in scale-up, low cost-effectiveness, potential immunogenicity and systematic toxicity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous findings also indicated that cationic peptidomimetics with lipidation could kill bacteria with greater potency by disrupting bacterial membranes. 4146 Thus, we hypothesized that hydantoin compounds bearing cationic groups and lipid tails (Figure 2, D2) would be membrane active, similar to the mechanism of action of HDPs. As such, they could interact with bacterial membranes and kill bacterial pathogens through bacterial membrane disruption.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently developed a library of small compounds based on the reduced amide scaffold (Fig. 1) [20]. All compounds share the same backbone.…”
Section: Introductionmentioning
confidence: 99%